2007
DOI: 10.1248/bpb.30.1878
|View full text |Cite
|
Sign up to set email alerts
|

Isobavachalcone, a Chalcone Constituent of Angelica keiskei, Induces Apoptosis in Neuroblastoma

Abstract: Six chalcones from Angelica keiskei KOIDZUMI (Ashitaba in Japanese) and two chalcones from Humulus lupulus L. (hop) were examined for their cytotoxicity in two human neuroblastoma cell lines (IMR-32 and NB-39) and normal cells (primary culture of rat cerebellar granule cells) by [3-(4,5)-dimethyl-2-thiazolyl]-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. All chalcones exhibited cytotoxicity against neuroblastoma cells, and two of them (isobavachalcone and xanthoangelol H) had no effect on normal cells even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 32 publications
2
82
0
1
Order By: Relevance
“…Another component of this plant, isobavachalcone (15), induced apoptosis in neuroblastoma by downregulation of pro-caspase 3 and 9 followed by upregulation of cleaved caspase 3 and 9 and Bax induction, similar to the effects of chalcone (10) in human bladder cancer cells [128,158]. Moreover, no cytotoxicity was observed against nontransformed cells [128]. A similar mechanism was described for isolespeol (39), isolated from the traditional starch crop Artocarpus communis cultivated in tropical and subtropical regions [33], in human liposarcoma SW-872 cells [187,188].…”
Section: Chalcones As Inducers Of Cell Death Mechanismsmentioning
confidence: 61%
See 1 more Smart Citation
“…Another component of this plant, isobavachalcone (15), induced apoptosis in neuroblastoma by downregulation of pro-caspase 3 and 9 followed by upregulation of cleaved caspase 3 and 9 and Bax induction, similar to the effects of chalcone (10) in human bladder cancer cells [128,158]. Moreover, no cytotoxicity was observed against nontransformed cells [128]. A similar mechanism was described for isolespeol (39), isolated from the traditional starch crop Artocarpus communis cultivated in tropical and subtropical regions [33], in human liposarcoma SW-872 cells [187,188].…”
Section: Chalcones As Inducers Of Cell Death Mechanismsmentioning
confidence: 61%
“…In addition, apoptosis induction through ROS generation by xanthoangelol (33), a major constituent of Angelica keiskei, was described by Motani et al in neuroblastoma [121]. Another component of this plant, isobavachalcone (15), induced apoptosis in neuroblastoma by downregulation of pro-caspase 3 and 9 followed by upregulation of cleaved caspase 3 and 9 and Bax induction, similar to the effects of chalcone (10) in human bladder cancer cells [128,158]. Moreover, no cytotoxicity was observed against nontransformed cells [128].…”
Section: Chalcones As Inducers Of Cell Death Mechanismsmentioning
confidence: 77%
“…In this study we compared the cytotoxicity of naringenin and 8-prenylnaringenin ( Figure 1) against normal fibroblasts and U-118 MG glioma cells due to reports that substitution of the prenyl group increases the hydrophobicity of flavonoids and may led to its higher cellular accumulation [26] and in consequence higher toxicity against cancer cells [27]. Neutral red assay showed that both flavonoids exerted stronger inhibitory effect on the cancer cell line as compared with normal cells (Figure 2).…”
Section: Cytotoxicity Of Naringenin and 8-prenylnaringeninmentioning
confidence: 99%
“…They have serve as lead compounds for the discovery of new anti-inflammatory, anti-infective, anti-cancer and antioxidant agents [24]. A literature report shows that chalcones are capable of inducing the death of cancer cells through apoptosis, as well as subsiding the mitochondrial membrane potential [25][26][27].…”
Section: Introductionmentioning
confidence: 99%